Involvement of intramuscular interstitial cells of Cajal in neuroeffector transmission in the gastrointestinal tract - Ward, Sean M (Blackwell Science Inc, 2006)
Specialized cells known as interstitial cells of Cajal (ICC) are distributed in specific locations within the tunica muscularis of the gastrointestinal (GI) tract. ICC serve as electrical pacemakers, provide pathways for the active propagation of slow waves, are mediators of enteric motor neurotransmission and play a role in afferent neural signalling. Morphological studies have provided evidence that motor neurotransmission in the GI tract does not occur through poorly defined structures between nerves and smooth muscle, but rather via specialized synapses that exist between enteric nerve terminals and intramuscular ICC or ICC-IM. ICC-IM are coupled to smooth muscle cells via gap junctions and post-junctional responses elicited in ICC-IM are conducted to neighbouring smooth muscle cells. Electrophysiological studies from the stomachs and sphincters of wild-type and mutant animals that lack ICC-IM have provided functional evidence for the importance of ICC in cholinergic excitatory and nitrergic inhibitory motor neurotransmission. Intraperitoneal injection of animals with Kit neutralizing antibody or organ culture of gastrointestinal tissues in the presence of neutralizing antibody, which blocks the development and maintenance of ICC, has provided further evidence for the role of ICC in enteric motor transmission. ICC-IM also generate an ongoing discharge of unitary potentials in the gastric fundus and antrum that contributes to the overall excitability of the stomach.